Organizational Structure Analysis Via the dimension of the Organic synthesis - محمد اياد طاهر; حميد مهند طلب (Journal of Economics and Administrative Sciences, 2014)
The study focused on the identification of the natural relation between the organizational components, and the most important is the organizational structure, which not hid its effect on each function and operation of the organizational structure through commanding the individual craters and its forms according to the requirement of these function, also it has relation with an organic synthesis that between the dimensions of the organic synthesis and the practice side in the commission of Integrity. The problem of the research pensioned in some questions about hypothesis and theoretical parts, in which they go a mention about the hypothesis questions is to use all the knowledge’s in this atmosphere and they explain the second by some practical.